An observational study to compare the utilisation of computed tomography colonography with optical colonoscopy as the first diagnostic imaging tool in patients with suspected colorectal cancer. Issue 9 (September 2020) - Rua, T.; Watson, H.; Malhotra, B.; Turville, J.; Razavi, R.; Peacock, J.L.; McCrone, P.; Goh, V.; Shearer, J.; Griffin, N.
Abstract : Aim: To evaluate the clinical and cost implications of using computed tomography colonography (CTC) compared to optical colonoscopy (OC) as the initial colonic investigation in patients with low-to-intermediate risk of colorectal cancer (CRC). Materials and methods: A non-randomised, prospective single-centre study recruited 180 participants to compare the cost implications of two clinical pathways used in the diagnosis of low-to-intermediate risk of CRC that differ in the initial diagnostic test, either CTC or OC. Costs were compared using generalised linear models (GLM) and combined with quality-adjusted life years (QALYs, based on the EQ-5D-5L) to estimate cost-effectiveness at 6 months post-recruitment. Secondary outcomes assessed access to care and patient satisfaction. Results: Mean (SD, n ) cost at 6 months post-recruitment per participant was £991 (£316, n =105) for the OC group and £645 (£607, n =68) for the CTC group, leading to an estimated cost difference of –£370 (95% CI: –£554, –£185, p <0.001). Assuming a £20, 000 willingness-to-pay per QALY threshold, there was a 91.4% probability of CTC being cost-effective at month 6. The utilisation of CTC led to improved access to care, with a shorter mean time from referral from primary care to results (6.3 days difference, p =0.005). No differences in patient satisfaction were detected between both groups. Conclusion: The utilisation of CTC as the first-line investigation for patients with low-to-intermediate risk of CRC has the potential to release OC capacity, of pivotal importance for patients more likely to benefit from an invasive diagnostic approach. Highlights: CRC is the third most common cancer in the UK and the second cause of cancer death. An annual increase of 10% to 15% in the demand for colonic investigations is forecasted. CTC improved access to care for patients with suspected colorectal cancer. The use of CTC as the first diagnostic test saved money to the healthcare system. The use of CTC released OC capacity for patients more likely to benefit from an invasive test.